Bioteknologi Pembuatan Pestisida Organik dari Bahan Alam: Solusi Ekologis untuk Pertanian Berkelanjutan di Desa Medana Kabupaten Lombok Utara - Salma Apipah; Baiq Muli Harisanti; Any Fatmawati; Lalu Habiburrahman; Saidil Mursali; Sucika Armiani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Continuous use of chemical pesticides can increase the risk of environmental pollution, residues in agricultural products, health problems, and pest resistance. In Medana Village, members of the Women Farmers Group (KWT) need alternative plant pest control that is easy to make, cheap, and more environmentally friendly. This community service activity aims to improve the knowledge and skills of KWT members in making organic pesticides from natural ingredients and kitchen ingredients. The activity was carried out in Medana Village, Tanjung District, North Lombok Regency through socialization, demonstrations, direct practice, mentoring, and participatory evaluation. The materials used included turmeric, rice washing water, tobacco, coffee grounds, and shallot skins. Participants were guided to make three simple formulations, namely a mixture of turmeric and rice washing water, a mixture of tobacco and coffee grounds, and a soaking of shallot skins. The solution was fermented for 1x24 hours, filtered, diluted, and then applied to plants. The results of the activity showed that participants were able to understand the benefits of organic pesticides, recognize local materials with bioactive potential, and practice the stages of making pesticides independently. Based on observations and discussions, participants expressed interest in applying organic pesticides to yard plants and agricultural land as an effort to reduce dependence on chemical pesticides. This activity contributed to strengthening the capacity of the Women's Farmers' Group (KWT) in managing environmentally friendly agriculture based on local materials.